Report on Dry Land Farming Trends and Prospects - Planning Commission (Planning Commission, 1986)
It is now widely recognized that agricultural growth achieved so far, particularly in the post-green revolution period, has led to widening of regional disparities including between dry land and irrigated areas. Even after realising the entire irrigation potential in the country, about half of the area will still remain unirrigated. Therefore, development of dry land farming is important on considerations of both growth and equity. In the Seventh Five Year Plan, therefore, very high priority has been accorded to development of dry land farming.
Government of India Planning Commission (Perspective Planning Division)
Government of India Planning Commission (Perspective Planning Division)